Association Studies of Common Variants of TCF4 Gene Conferring Risk of Schizophrenia in Pakistani Patients: Association Studies of Common Variants of TCF4 Gene - Ijaz, Faiza; Ghaffar, Nabila; Mazhar, Ayesha; Ahmad Khan, Muhammad Khalil; Tariq, Muhammad Akram (Pakistan Journal of Health Sciences, 2023)
Schizophrenia is a psychiatric disorder and it is strongly inherited disease with a heritability of 80% or more. Rare genetic mutations are more frequent in schizophrenia patients. These genetic variations interfere with brain development and include hundreds of distinct genes. Transcription factor 4 (TCF4) has been emphasized as major players for disruption of brain development as well as function and consequently, the onset of schizophrenia. The dysregulation of TCF4 gene expression in brain affects the process of pre pulse inhibition (PPI) and consequently profound reduction in sensor motor gating that may results in to the onset of schizophrenia. Objective: To find out the genetic association of common variants of TCF4 gene conferring risk of schizophrenia. Methods: It was a case control study in which statistically significant number of blood samples of confirmed diagnosed schizophrenic patients as well as age matched healthy control subjects were analyzed to screen out selected Single Nucleotide Polymorphisms (rs9960767, rs4309482, rs12966547, and rs2958182) of TCF4 gene for their association with schizophrenia. Results: Out of these four SNPs rs9960767 and rs4309482 were significantly associated with schizophrenia. p-values for SNPs rs12966547 and rs2958182 were greater than 0.05 in both healthy controls and in patients. Conclusions: The results of this study offer compelling evidence for the link between particular TCF4 gene polymorphisms and schizophrenia. Two SNPs, rs9960767 and rs4309482, were found to have a strong correlation with schizophrenia in the research population, according to the analysis.